Uma análise dos mediadores curriculares do programa São Paulo faz Escola: um olhar sobre o consumo - Rocha, Julciane Castro da (2011)
This research aims to identify, analyze and discuss, in light of theory, the different manners used to approach the subject of consumption in the Portuguese Language curriculum mediators in Middle School, which were created by the São Paulo Department of Educational Affairs, for the São Paulo Faz Escola Program, seeking to find answers to the following questions: What aspects of the subject of consumption are presented in the curriculum? Which aspects are missing? What kind of people are students expected to be after having this exact curriculum? To this end, the Portuguese Language Teacher s and Student s Books for Middle School were chosen as study objects. The qualitative method was selected for this research, along with some quantitative method akin, which were held through the exploratory research. Document retrieval was used to approach the universe of this study. In order to achieve the proposed goals, five chapters were developed, the first three addressing the theoretical basis. In the first chapter, a historical review of Curriculum Studies was made, so as to situate our research within the critical theories later on. Still in this chapter, the concepts that underlie our research are introduced, such as prescribed curriculum and the curriculum presented to the teachers staff (GIMENO SACRISTÁN, 2000). In the second chapter, the thinking of some authors that focused on reasoning about education as a privileged space for awareness, building citizenship and social transformation, as Freire (2001, 2002, 2005), Cortella (2008), among others, are presented. The third chapter is devoted to the deepening socio-historical and theoretical work on consumption, through the writings of Hobsbawm (2000), Marx (1996), Löwy (2000), Barbosa (2008) and Lara (2009). The fourth chapter focuses on the contexts of our research, data collection and interpretation of results in light of theory. In the last chapter, considerations about the process of this research are made, at the same time that the results analysis and our outlook on including the subject of consumption in the curriculum are presented with a critical eye